Diversi: Anak yang Berhadapan Dengan Hukum - Herman Balla (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
This Research discusses diversion implementation by the police station of Sidenreng Rappang as the alternative to resolving criminal cases of children in conflict with the law. As for that to be special-purpose from this research: the first, describe the diversion implementation as the alternative resolving criminal case children in conflict with the law; the second, Describe the form of diversion as mediation penal that implementation in Sidenreng Rappang Police station; the third Conclude any obstacles faced in diversion implementation as the alternative resolving criminal case children in conflict with the law of Sidenreng Rappang Police station. The result of this research is the implementation of diversion can be more optimal. In case to solve the problem of children especially child crime for guarantee legal certainty for children in conflict with the law. This process usually settles out of court, that is through diversion based on the approach of restorative justice in the Sidenreng Rappang region. Therefore, not many children have required to carry out criminal liability should the age children get construction according to their age.